Wavelet Analysis on the Sphere Spheroidal Wavelets - Mabrouk, Anouar Ben; Arfaoui, Sabrine; Rezgui, Imen (De Gruyter, 2017)
The goal of this monograph is to develop the theory of wavelet harmonic analysis on the sphere. By starting with orthogonal polynomials and functional Hilbert spaces on the sphere, the foundations are laid for the study of spherical harmonics such as zonal functions. The book also discusses the construction of wavelet bases using special functions, especially Bessel, Hermite, Tchebychev, and Gegenbauer polynomials.
Description based on print version record.
KU Select 2019: STEM Backlist Books
Keywords: Mathematics / Mathematical Analysis; Mathematics; Electronic books